Trends Among Jordanian TV Communicators in Employing Artificial Intelligence Applications in Newsrooms - AbuZaid, Qasim Zaid Ahmad; Alrajabi, Mah’d Ahmad Moh’d (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aims to discern the patterns of communication on Jordanian television, assess the level of information among communicators, and understand their expected behavior and performance, facilitated by the use of artificial intelligence applications in newsrooms. Methodology: This study employs the survey method and utilizes a questionnaire, targeting a purposive sample of 64 respondents working in the newsrooms of Jordanian television. Results: The study yielded several findings, with one of the most significant being that the knowledge of Jordanian TV communicators regarding the utilization of artificial intelligence applications in newsrooms was high, with a rate of 83.8%. Additionally, the attitudes of Jordanian television communicators toward employing artificial intelligence applications in newsrooms were positive, with a rate of 81.8%. Conclusion: The study recommends conducting additional surveys on the attitudes of communicators in Jordanian satellite channels regarding the utilization of artificial intelligence applications in newsrooms. Furthermore, there is a need for the Jordan Radio and Television Corporation to organize specialized workshops on the adoption of artificial intelligence applications in newsrooms.